2017
DOI: 10.2196/medinform.7883
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simulation Based on an Electronic Health Records Environment to Evaluate the Structure and Accuracy of Notes Generated by Medical Scribes: Proof-of-Concept Study

Abstract: BackgroundThe increasing adoption of electronic health records (EHRs) has been associated with a number of unintended negative consequences with provider efficiency and job satisfaction. To address this, there has been a dramatic increase in the use of medical scribes to perform many of the required EHR functions. Despite this rapid growth, little has been published on the training or assessment tools to appraise the safety and efficacy of scribe-related EHR activities. Given the number of reports documenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…[24][25][26][27][28] However, some have suggested that using scribes results in lost nuance and cognitive processing time, 29 and relatively little is known about the safety and accuracy of scriberelated documentation. 30 Moreover, scribes may not always be financially feasible. Therefore, additional strategies to improve EHR use warrant further investigation.…”
Section: Background and Significancementioning
confidence: 99%
“…[24][25][26][27][28] However, some have suggested that using scribes results in lost nuance and cognitive processing time, 29 and relatively little is known about the safety and accuracy of scriberelated documentation. 30 Moreover, scribes may not always be financially feasible. Therefore, additional strategies to improve EHR use warrant further investigation.…”
Section: Background and Significancementioning
confidence: 99%
“…5 Prior studies suggest deterioration with note veracity, which is potentially further confounded by these factors. 7 This concern is also exacerbated by the observation that the supervision of scribes is varied and unstructured. 12 This might be exaggerated by physical separation of scribes from their providers, reducing the opportunity for active collaboration and communication.…”
Section: Discussionmentioning
confidence: 99%
“…interscribe variability in the data elements recorded in their individual notes. 7,8 With the outbreak of the novel coronavirus disease 2019 (COVID-19), there has been a rapid transition to virtual care delivery, telecommuting, and redeploying personnel to meet evolving needs. 9 This raises the concern that when providers are still employing scribes, the scribes have been thrust into new clinical care delivery models with little training.…”
mentioning
confidence: 99%
“…Two studies reviewing the quality of scribe documentation found significant variation in quality. 10,11 When supervisors spend time to improve scribe documentation, they are educating the scribes about appropriate use of medical language and the relative pertinence of information (e.g., choosing pertinent positives and negatives), which are also medical student milestones for developing clinical reasoning. This begs the question of whether this Btraining^time might be better spent with medical students.…”
Section: Cribe Role and Overlap With Medical Student Learning Opportumentioning
confidence: 99%